Innovation in a Circular Economy: Conceptual, empirical and policy underpinnings for transition through an eco-innovation pathway - Silva, Ana Isabel de Jesus Correia Fernandes Oliveira (2020)
As the world seeks answers to the defining challenges of climate change and environmental sustainability, several hypotheses are being canvased in the search for a solution to decouple economic growth and social development from resource exploitation. Among those, the circular economy (CE) emerged as an operational response defined by its opposition to a harvesting-wasting economic model, proposing instead restorative and regenerative activities. But reconfiguring existing paradigms is not trivial. Aligning innovation activities with more sustainable paths is a central requirement for the desired socio-techno-economic paradigm shift. This work proposes that a new pathway is needed for gearing the sustainable innovation agenda towards a CE, and foster structural change. CE-inducing eco-innovation (EI) must, however, be monitored and measured, and implications to socio-cultural agents, organisational strategies and policy priorities have to be bore in mind, if we are to ascertain if progress is being made. As CE and the EI – CE nexus research is still in its early days, this work adds to the discussion by contributing (1) to the theoretical development of these concepts and their interrelations; (2) to the empirical definition of pro CE EI proxies; and (3) to the prospective anticipation of CE developments. Within the sustainability debate, and using an innovation studies perspective, this research adopted a mixed methods approach, using both quantitative and qualitative methods such as literature reviews, bibliometrics, patent and trademark analysis (using the specific case of Portugal), and foresight techniques (Delphi study). The overall findings suggest that CE’s main ideas are arguably timely. CE’s establishment within the sustainability debate seems, nevertheless, dependent on overcoming short term barriers constraining its further development, of technological and economic nature, but also of a socio-cultural kind. CE is argued as a multidimensional, multi-actor approach reliant on “systemic transformative” innovation, thus dependent on a combination of “harder”, (technological, R&D-driven), and “softer” (non-technological change in social and business culture) knowledge. The empirical diagnosis of an innovation system’s pro circularity tendencies proved to be informative as to assess convergence to circularity. In the Portuguese case, it successfully shed light on ongoing dynamics related with signs of effective transformation towards CE activities, even if highlighting structural limitations associated with systemic failures regarding actors and networks. Redirecting innovation systems towards a more “circular” paradigm is, therefore, deeply dependent on an institutional “coordination role” enabling “framework conditions” directly linked to a systemic action. That is, associating bottom-up measures to top-down policies in a coherent strategic roadmap, in order to avoid mismatches and contradictory incentives. This pointed to the usefulness of rethinking innovation policy design. In one hand, to address market and system failures, leading to underinvestment and lack of connectivity in innovation. In the other hand, to promote the diffusion of CE related information for enterprises and civil society, in order to encourage market awareness and change mind-sets towards “circular” behaviours. As the conceptual and practical implementation challenge remains pressing, this work added important underpinnings for fine-tuning a CE inducing “policy mix”.